Assessing the Effects of EU Trade Preferences for Developing Countries - Maria Persson; Fredrik Wilhelmsson (Lund University, School of Economics and Management, Department of Economics, 2006)
Since the 1960's, the EU has offered trade preferences to developing countries in a complex set of systems. Broadly these systems can be divided into preferences for African, Caribbean and Pacific (ACP) countries, Mediterranean preferences and the Generalised System of Preferences (GSP). We construct a detailed database over these trade preferences and use it to assess whether they have had an effect on developing countries' exports and whether the systems have had different impact on exports. To achieve this we also estimate the effect of the successive EU enlargements on exports from developing countries. A gravity model taking into account the evolution of developing countries' exports is estimated on a large sample of EU importers and developing country exporters over the period 1960-2002. The main findings are that certain preference systems have had large effects—the largest are found for the ACP countries, where the preferences increase exports by about 30 %, followed by Mediterranean countries—and that, countries joining the EU, ceteris paribus, import less from developing countries as they become members.
Keywords: C23; F13; 330; EU trade preferences; Trade; Developing Countries; Gravity model